Zn-Fe-P chemical plating gradient abrasion-resistant layer and preparation method thereof
By using Zn-Fe-P electroless plating gradient anti-wear layer on carbon steel components such as electric power tools, the shortcomings of the prior art to protect carbon steel components under abrasion conditions are solved, high wear resistance and corrosion resistance are achieved, and the service capacity of the components is significantly improved.
Patent Information
- Application Number
- CN202411567167.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to effectively protect carbon steel components such as power tools under abrasive conditions. The hot-dip galvanized layer is not corrosion-resistant and wear-resistant in high-temperature, high humidity, high chlorine and high wind environments.
Zn-Fe-P electroless plating gradient anti-wear layer is used, and the passivation layer is divided into a passivation layer, a low-iron Zn-Fe-P electroless plating layer and a high-iron Zn-Fe-P electroless plating layer with a corrosion potential from low to high, thereby improving the wear resistance and corrosion resistance of metal components.
The high wear resistance and corrosion resistance of metal components under abrasion conditions are achieved. Through the combined action of the gradient structure and the passivation layer, the service capacity of carbon steel components such as power tools is significantly improved.
Smart Images

Figure CN119753651A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface treatment, in particular to an environmentally friendly and low-cost Zn-Fe-P chemical plating gradient anti-wear layer and a preparation method thereof. Background Art
[0002] As the most important basic material, carbon steel is widely used in industries such as electricity, communications, chemicals, automobiles, and national defense. For example, U-shaped rings, ball head hanging rings and other power fittings are exposed to various meteorological conditions all year round, and corrosion occurs all the time. Breeze vibration, dancing, icing, sub-span vibration, wire de-icing and jumping, etc., cause wear of line fittings to varying degrees, which requires power fittings to have both corrosion and wear conditions. The commonly used hot-dip galvanized layer is neither corrosion-resistant nor wear-resistant in the coastal environment of high temperature, high humidity, high chlorine, and strong winds, resulting in frequent cases of abrasion failure of power fittings. Therefore, the development of an environmentally friendly, low-cost, wear-resistant layer with good performance has significant practical significance.
[0003] In order to improve the corrosion resistance of carbon steel and other components, some people have studied zinc alloy coatings such as Zn-Ni, Zn-Co, and Zn-Fe. Among them, the Zn-Fe alloy coating has the lowest cost and is more environmentally friendly. Structure determines performance. Zhang Sifang found that as the Fe content in the Zn-Fe alloy coating gradually increases from less than 0.03wt% to 95wt%, the coating structure also changes from η phase, ζ phase, and γ phase to α phase, which makes the performance of the Zn-Fe alloy layer very different (Zhang Sifang, The influence of Fe content in zinc-iron coating on product coating structure and performance, 2013 National Cold Rolled Strip Production Technology Exchange Conference, 2013: 125-128). When the Fe content is ≤1wt%, its corrosion resistance can be greatly improved by passivation. For example, Li Xueyuan et al. passivated the Zn-Fe deposit with an Fe content of 0.3wt% to 0.9wt%. After 1488 hours of neutral salt spray test, no red rust was observed (Li Xueyuan et al., Study on Electrodeposition and Corrosion Resistance of Zn-Fe Alloy Coating, Acta Aeronautica Sinica, 2000, 21: S58-S61). At this time, Zn-Fe is in η phase (Yang Fangzu et al., Relationship between Iron Content and Properties of Zinc-Fe Alloy Coating, Electroplating and Finishing, 1992, 11 (1): 11-14), and the hardness value is only 120 to 130 HV (Zeng Xiangde, 20 Years of Application Practice of Environmentally Friendly High Corrosion Resistance Zinc-Fe Alloy Electroplating Process, Surface Engineering Information, 2010, 5: 10-13). Obviously, the Zn-Fe alloy layer with Fe content ≤1 wt% has good corrosion resistance, but poor tribological properties. When the Fe content is 23 wt%≤≤28wt%, it presents the γ phase and the hardness value can reach 450~550HV (Zhang Sifang, Influence of Fe content of zinc-iron coating on product coating structure and performance, 2013 National Cold Rolled Strip Production Technology Exchange Conference, 2013: 125-128). However, due to the high iron content, conventional passivation cannot be performed, which affects its corrosion resistance (Cui Ping et al., Research on electroplating of zinc-iron alloy with low iron content in alkaline solution, Materials Protection, 2008, 41 (9): 31-33, 51). Therefore, the Zn-Fe alloy layer at this time has certain tribological properties, but poor corrosion resistance.
[0004] Patent documents CN104120466A, CN105442000A, CN109137016A, CN1162571C, etc. prepared Zn-Fe alloy coatings with low iron content in acidic or alkaline baths, and patent documents CN117535744A and CN101545125A prepared Zn-Fe alloy coatings with iron contents of 12% to 18% and 17% to 20%, respectively. Although the existing patents have studied the deposition of Zn-Fe alloys with low and high iron contents, on the one hand, a single Zn-Fe alloy coating is obviously difficult to meet the requirements of carbon steel components such as power fittings in abrasive conditions; on the other hand, the above technologies are all electrodeposition technologies, and there are very few studies on the preparation of Zn-Fe-P alloys using chemical plating technology. Summary of the invention
[0005] The present invention aims to overcome the defects of the above-mentioned prior art and provide an environmentally friendly and low-cost Zn-Fe-P chemically plated gradient anti-wear layer and a preparation method thereof, so as to improve the service capacity of metal components such as power fittings in abrasive conditions.
[0006] To this end, the present invention adopts the following technical solution.
[0007] In a first aspect, the present invention provides a Zn-Fe-P chemical plating gradient anti-wear layer, which is divided into a passivation layer, a low-iron Zn-Fe-P chemical plating layer and a high-iron Zn-Fe-P chemical plating layer from the surface to the inside, forming a gradient plating layer with a corrosion potential from low to high; The low-iron Zn-Fe-P chemical plating layer has an iron content of 0.03wt%-1.0wt%, a thickness of 8μm-18μm, and a hardness of 120-130HV; The high iron Zn-Fe-P chemical plating layer has an iron content of 5wt%-30wt%, a thickness of 8μm-18μm, and a hardness of 450-550HV.
[0008] Furthermore, the iron content in the low-iron Zn-Fe-P chemical plating layer is preferably 0.1wt%-1.0wt%, and the iron content in the high-iron Zn-Fe-P chemical plating layer is preferably 7wt%-20wt%.
[0009] Furthermore, the high iron Zn-Fe-P chemical plating layer is prepared from the following high iron solution: The high iron solution comprises zinc oxide, sodium hydroxide, ammonium ferrous sulfate hexahydrate, sodium hypophosphite, a multi-component complex system, a combined brightener and a stabilizer; The concentration of the zinc oxide is 8-15 g / L; The concentration of the sodium hydroxide is 50-120 g / L; The concentration of the ammonium ferrous sulfate hexahydrate is 18-40 g / L; The concentration of the sodium hypophosphite is 10-30 g / L; The multi-component complex system is an alkaline system, which is a mixture of tetraethylenepentamine, triethylenetetramine, ethylenediamine, sodium gluconate and triethanolamine; the concentration of tetraethylenepentamine is 10-30mL / L, the concentration of triethylenetetramine is 0-20mL / L, the concentration of ethylenediamine is 0-20mL / L, the concentration of sodium gluconate is 10-30g / L, and the concentration of triethanolamine is 5-20mL / L.
[0010] Furthermore, in the high iron solution, the concentration of the ammonium ferrous sulfate hexahydrate is preferably 20-30 g / L, the concentration of the sodium hypophosphite is preferably 15-26 g / L, the concentration of tetraethylene pentamine is preferably 15-25 mL / L, the concentration of triethylenetetramine is preferably 0-15 mL / L, the concentration of ethylenediamine is preferably 0-15 mL / L, the concentration of sodium gluconate is preferably 15-20 g / L, and the concentration of triethanolamine is preferably 10-15 mL / L.
[0011] Furthermore, the combined brightener is a mixture of benzylpyridinium carboxylate and one or more of vanillin, piperonal, heliotropein, polyethylene glycol, and butynediol; in the combined brightener, the concentration of benzylpyridinium carboxylate is 0.05-0.2 mL / L (preferably 0.06-0.12 mL / L), the total concentration of the mixture of one or more of vanillin, piperonal, and heliotropein is 50-150 mg / L (preferably 60-100 mg / L), and the total concentration of the mixture of one or more of polyethylene glycol and butynediol is 40-120 mg / L (preferably 50-80 mg / L).
[0012] Furthermore, the stabilizer is one or more of potassium sodium tartrate, sodium ascorbate, sodium sulfite, manganese dichloride, rare earth salts, etc.; the stabilizer is 8-20 g / L (preferably 10-15 g / L) of potassium sodium tartrate, 0.5-3 g / L (preferably 0.8-2 g / L) of sodium ascorbate, 5-20 mg / L (preferably 8-12 mg / L) of sodium sulfite, 0-5 g / L (preferably 0-3 g / L) of manganese dichloride, and the rare earth salt is one or more of nitrates, acetates, sulfates and chlorides of rare earth elements, taking 0.001-0.025 mol / L.
[0013] Furthermore, the high iron solution also includes other additives, which are tetrahydrothiazolidinethione and surfactants; tetrahydrothiazolidinethione is 0-20 mg / L (0-5 mg / L when the substrate of the metal component is carbon steel or copper substrate, and 10-20 mg / L when the substrate of the metal component is aluminum substrate); the surfactant includes one or more of chlorhexidine, OP emulsifier, sodium dodecyl sulfate, and sodium dodecyl sulfonate, with a total concentration of 0.04-0.8 g / L.
[0014] Furthermore, the low-iron Zn-Fe-P chemical plating layer is prepared from the following low-iron solution: The low-iron solution comprises zinc oxide, sodium hydroxide, ammonium ferrous sulfate hexahydrate, sodium hypophosphite, a multi-component complex system, a combined brightener and a stabilizer; The concentration of the zinc oxide is 8-15 g / L; The concentration of the sodium hydroxide is 50-120 g / L; The concentration of the ammonium ferrous sulfate hexahydrate is 1.5-15 g / L; The concentration of the sodium hypophosphite is 10-30 g / L; The multi-component complex system is an alkaline system, which is a mixture of sodium salicylate, sodium citrate or ammonium citrate, pyridine, sodium gluconate and triethanolamine; the concentration of sodium salicylate is 3-18 g / L, the concentration of sodium citrate or ammonium citrate is 10-30 g / L, the concentration of pyridine is 0-18 g / L, the concentration of sodium gluconate is 10-30 g / L, and the concentration of triethanolamine is 10-30 mL / L.
[0015] Furthermore, in the low-iron solution, the concentration of ammonium ferrous sulfate hexahydrate is preferably 2-8 g / L, the concentration of sodium hypophosphite is preferably 15-26 g / L, the concentration of sodium salicylate is preferably 5-12 g / L, the concentration of sodium citrate or ammonium citrate is preferably 12-25 g / L, the concentration of pyridine is preferably 0-12 g / L, the concentration of sodium gluconate is preferably 15-20 g / L, and the concentration of triethanolamine is preferably 15-25 mL / L.
[0016] Furthermore, the low-iron solution also includes a surfactant; the surfactant includes one or more of chlorhexidine, OP emulsifier, sodium dodecyl sulfate, and sodium dodecyl sulfonate, and the total concentration is 0.04-0.8 g / L.
[0017] Furthermore, the passivation layer is prepared from a solution consisting of chromium nitrate nonahydrate, sodium nitrate, sodium oxalate, sodium malonate, maleic anhydride, cobalt nitrate hexahydrate and amino silicon: the concentration of the chromium nitrate nonahydrate is 40-80 g / L; the concentration of the sodium nitrate is 5-20 g / L; the concentration of the sodium oxalate is 10-20 g / L; the concentration of the sodium malonate is 10-20 g / L; the concentration of the maleic anhydride is 1-2 g / L; the concentration of the cobalt nitrate hexahydrate is 5-8 g / L; and the concentration of the amino silicon is 3-5 mL / L.
[0018] In a second aspect, the present invention provides a method for preparing a Zn-Fe-P chemically plated gradient anti-wear layer, the steps of which are as follows: The metal component is first subjected to a pretreatment of degreasing-washing-rust removal-washing-activation, and then immersed in a high-iron solution for deposition after washing to obtain a metal component covered with a high-iron Zn-Fe-P chemical plating layer, and then directly immersed in a low-iron solution for deposition without washing, so that the high-iron Zn-Fe-P chemical plating layer is covered with a low-iron Zn-Fe-P chemical plating layer, and then subjected to light exposure-washing-passivation-washing-sealing-drying after washing, so that the low-iron Zn-Fe-P chemical plating layer is covered with a passivation layer, thereby obtaining a desired Zn-Fe-P chemical plating gradient anti-wear layer on the surface of the metal component; The temperature of deposition in high iron solution is 40-80°C, and the time is 20-40 minutes; the temperature of deposition in low iron solution is 40-80°C, and the time is 30-60 minutes; during passivation treatment, nitric acid or sodium hydroxide is used to adjust the pH value of the solution to 2.0-2.5, the temperature is 20-45°C, and the time is 30-60s.
[0019] Furthermore, the base material of the metal component is carbon steel, stainless steel, copper or aluminum.
[0020] The above degreasing, rust removal and activation are aimed at obtaining a fresh substrate surface. Conventional treatment processes are sufficient. A 0.2-0.5% dilute nitric acid solution can be used for polishing, and trivalent chromium passivation or chromium-free passivation can be used for passivation.
[0021] The beneficial effects of the present invention are as follows: 1. By utilizing the Fe content gradient in the coating from the surface to the inside, a passivation layer and a structural gradient from η phase to γ phase are formed on the metal component, thereby forming a performance gradient of the three-layer structure: the hardness increases from 120-130 HV when the outer layer has a low Fe content to 450-550 HV when the inner layer has a high Fe content, thereby enhancing its wear resistance.
[0022] 2. The corrosion resistance of the three-layer structure to the carbon steel substrate is guaranteed from three aspects. First, the Zn-Fe-P layer acts as a sacrificial anode to provide cathodic protection to the carbon steel substrate. Secondly, the passivation of the outer layer with low Fe content is used to form a passivation film to ensure that the three-layer structure has good corrosion resistance. Finally, the potential difference between the coating and the steel substrate is gradually shortened by the gradual increase of Fe content from the surface to the inside, so that it still has a certain corrosion resistance after the outer layer is gradually consumed.
[0023] 3. Using the difference in complexing ability and Fe 2+ When preparing a high Fe content Zn-Fe-P layer, the Fe 2+ Weak complexation, with Zn 2+ Strong complexing system (such as tetraethylenepentamine, etc.), while using high Fe 2+ concentration; when preparing a low Fe content Zn-Fe-P layer, the Fe 2+ Strong complexation with Zn 2+ Weakly complexed complex systems (such as sodium citrate or ammonium citrate, etc.), while using low Fe 2+ concentration.
[0024] 4. Utilize the antioxidant effects of sodium ascorbate, sodium sulfite, manganese dichloride, etc., and the complex system to Fe 2+ The complexation effect inhibits the Fe 2+ oxidation; use potassium sodium tartrate to mask impurity ions; rare earth ions can be adsorbed on the surface of aluminum, hindering Al3+ It can enter the plating solution to produce a poisoning effect, and can also form stable rare earth citrate anions with the complexing agent citrate to reduce the generation of precipitation, which is beneficial to improving the stability of the chemical plating solution.
[0025] 5. Environmental advantages. Compared with hot-dip galvanizing, the 40-80℃ Zn-Fe-P chemical plating process replaces the current 450℃ hot-dip galvanizing process, which has obvious advantages of low carbon and low energy consumption. Compared with Zn-Ni electrodeposition and Zn-Ni-P chemical plating, the Fe 2+ Replace Ni 2 + , with good environmental properties.
[0026] 6. Low cost advantage. Zn in the bath 2+ with Fe 2+ Wide sources and low cost advantages.
[0027] 7. Adopt chemical plating process, easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the embodiments or technologies of the present invention, the drawings used in the embodiments or technical descriptions are briefly introduced below.
[0029] Figure 1 This is a schematic diagram of the structure of the anti-corrosion layer prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention.
[0031] Example 1 A 10×20×2 mm Q235 test piece was polished with #2000 sandpaper, washed with deionized water, and then subjected to pretreatments such as degreasing-washing-rust removal-washing-activation. After washing, it was immersed in a high iron solution for deposition.
[0032] The composition of the high iron solution is: 10g / L zinc oxide, 100g / L sodium hydroxide, 30g / L ammonium ferrous sulfate hexahydrate, 24g / L sodium hypophosphite, 25mL / L tetraethylenepentamine, 5mL / L ethylenediamine, 20g / L sodium gluconate, 15mL / L triethanolamine in the multi-component complex system, 0.1mL / L benzylpyridinium carboxylate, 80mg / L vanillin, 60mg / L polyethylene glycol in the combined brightener, 15g / L potassium sodium tartrate, 2g / L sodium ascorbate, 50mg / L sodium sulfite, 3g / L manganese dichloride in the stabilizer, 0.002mol / L rare earth salt cerium sulfate, and 0.15g / L sodium dodecyl sulfate as an additive. The water bath temperature is 65°C. After 30 minutes, a bright and smooth coating is obtained on the surface of the Q235 test piece, that is, a Q235 test piece covered with a high iron Zn-Fe-P chemical coating is obtained.
[0033] The semi-quantitative analysis results of EDS showed that the zinc content of the obtained coating was 75.3wt.%, the iron content was 19.2wt.%, the phosphorus content was 2.1wt.%, and the remainder was others. The hardness value tested by a microhardness tester was 536HV.
[0034] The Q235 test piece coated with high-iron Zn-Fe-P chemical plating was immersed in a low-iron solution for deposition.
[0035] The composition of the low iron solution is: zinc oxide 10g / L, sodium hydroxide 100g / L, ammonium ferrous sulfate hexahydrate 4g / L, sodium hypophosphite 16g / L, sodium salicylate 8g / L, ammonium citrate 20g / L, sodium gluconate 15g / L, triethanolamine 15mL / L in the multi-component complex system, benzylpyridinium carboxylate 0.1mL / L, piperonal 70mg / L, butynediol 60mg / L in the combined brightener, potassium sodium tartrate 10g / L, sodium ascorbate 0.8g / L, sodium sulfite 8mg / L in the stabilizer, rare earth salt cerium sulfate 0.002mol / L, additive sodium dodecyl sulfate 0.1g / L. The water bath temperature is 75℃, and after 45 minutes, the surface of the test piece obtains a bright and smooth coating. The semi-quantitative analysis results of EDS showed that the zinc content of the surface coating was 96.6wt.%, the iron content was 0.8wt.%, the phosphorus content was 0.9wt.%, and the remainder was others. The hardness value tested by a microhardness tester was 134HV.
[0036] After low-iron solution deposition, it is washed with water, and then subjected to post-treatment steps such as light-washing-passivation-washing-sealing-drying to obtain the desired Zn-Fe-P chemical plating gradient anti-wear layer. The passivation process is: 60g / L chromium nitrate nonahydrate, 15g / L sodium nitrate, 10g / L sodium oxalate, 10g / L sodium malonate, 2g / L maleic anhydride, 6g / L cobalt nitrate hexahydrate, and 4mL / L amino silicon. The pH value is adjusted to 2 with nitric acid or sodium hydroxide, the temperature is 30°C, and the time is 40s.
[0037] Figure 1 The schematic diagram of the prepared "passivation film--Zn-Fe-P layer (low iron)--Zn-Fe-P layer (high iron)" anti-wear three-layer structure, the passivation film is the passivation layer, the Zn-Fe-P layer (low iron) is the low iron Zn-Fe-P chemical plating layer, and the Zn-Fe-P layer (high iron) is the high iron Zn-Fe-P chemical plating layer. With the increase of iron content from the surface to the inside, the potential difference between the anti-wear layer and the carbon steel substrate gradually shortens, thereby maintaining good corrosion resistance under the joint action of the passivation film, and the hardness value increases significantly with the evolution of the outer layer η phase to the inner layer γ phase, giving the anti-wear layer good wear resistance.
[0038] Comparative Example 1 (without passivation treatment) A 10×20×2 mm Q235 test piece was polished with #2000 sandpaper, washed with deionized water, and then subjected to pretreatments such as degreasing-washing-rust removal-washing-activation. After washing, it was immersed in a high iron solution for deposition. The composition of the high iron solution is: 10g / L zinc oxide, 100g / L sodium hydroxide, 30g / L ammonium ferrous sulfate hexahydrate, 24g / L sodium hypophosphite, 25mL / L tetraethylenepentamine, 5mL / L ethylenediamine, 20g / L sodium gluconate, 15mL / L triethanolamine in the multi-component complex system, 0.1mL / L benzylpyridinium carboxylate, 80mg / L vanillin, 60mg / L polyethylene glycol in the combined brightener, 15g / L potassium sodium tartrate, 2g / L sodium ascorbate, 50mg / L sodium sulfite, 3g / L manganese dichloride in the stabilizer, 0.002mol / L rare earth salt cerium sulfate, and 0.15g / L sodium dodecyl sulfate as an additive. The water bath temperature is 65°C. After 30 minutes, a bright and smooth coating is obtained on the surface of the Q235 test piece, that is, a Q235 test piece covered with a high iron Zn-Fe-P chemical coating is obtained.
[0039] The Q235 test piece covered with high-iron Zn-Fe-P chemical plating was immersed in a low-iron solution for deposition. The composition of the low-iron solution is: zinc oxide 10g / L, sodium hydroxide 100g / L, ammonium ferrous sulfate hexahydrate 4g / L, sodium hypophosphite 16g / L, sodium salicylate 8g / L, ammonium citrate 20g / L, sodium gluconate 15g / L, triethanolamine 15mL / L in the multi-component complex system, benzylpyridinium carboxylate 0.1mL / L, piperonal 70mg / L, butynediol 60mg / L in the combined brightener, potassium sodium tartrate 10g / L, sodium ascorbate 0.8g / L, sodium sulfite 8mg / L, rare earth salt cerium sulfate 0.002mol / L in the stabilizer, and sodium dodecyl sulfate 0.1g / L as an additive. The water bath temperature is 75℃, and a bright and smooth coating is obtained on the surface of the test piece after 45 minutes.
[0040] The sample of Example 1 and the sample of Comparative Example 1 were subjected to a 1000-hour neutral salt spray test. No red rust was observed on the sample of Example 1, but red rust was observed on the sample of Comparative Example 1.
[0041] Comparative Example 2 (without low iron solution deposition and passivation treatment) A 10×20×2 mm Q235 test piece was polished with #2000 sandpaper, washed with deionized water, and then subjected to pretreatments such as degreasing-washing-rust removal-washing-activation. After washing, it was immersed in a high iron solution for deposition.
[0042] The composition of the high iron solution is: 10g / L zinc oxide, 100g / L sodium hydroxide, 30g / L ammonium ferrous sulfate hexahydrate, 24g / L sodium hypophosphite, 10mL / L tetraethylenepentamine, 5mL / L ethylenediamine, 20g / L sodium gluconate, 15mL / L triethanolamine in the multi-component complex system, 0.1mL / L benzylpyridinium carboxylate, 80mg / L vanillin, 60mg / L polyethylene glycol in the combined brightener, 15g / L potassium sodium tartrate, 2g / L sodium ascorbate, 50mg / L sodium sulfite, 3g / L manganese dichloride in the stabilizer, 0.002mol / L rare earth salt cerium sulfate, and 0.15g / L sodium dodecyl sulfate as an additive. The water bath temperature is 65°C. After 30 minutes, a bright and smooth coating is obtained on the surface of the Q235 test piece, that is, a Q235 test piece covered with a high iron Zn-Fe-P chemical coating is obtained.
[0043] The semi-quantitative analysis results of EDS showed that the zinc content in the obtained coating was 81.4wt.%, the iron content was 12.5wt.%, the phosphorus content was 2.6wt.%, and the rest was other. The hardness value tested by microhardness tester was 467HV. 2+ The complexation is stronger than Fe 2+ When its concentration drops from 25 mL / L in the high-iron solution of Example 1 to 10 mL / L, it means that the free Zn in the solution 2+ The concentration of free Fe 2+ The concentration of is relatively reduced, resulting in changes in the composition and performance of the coating.
[0044] Example 2 A 10×20×2 mm 5052 aluminum specimen was polished with #2000 sandpaper, washed with deionized water, and then subjected to pretreatments such as degreasing-washing-rust removal-washing-activation. After washing, it was immersed in a high-iron solution for deposition.
[0045] The composition of the high iron solution is: 10g / L zinc oxide, 100g / L sodium hydroxide, 30g / L ammonium ferrous sulfate hexahydrate, 24g / L sodium hypophosphite, 20mL / L tetraethylenepentamine, 5mL / L ethylenediamine, 20g / L sodium gluconate, 15mL / L triethanolamine in the multi-component complex system, 0.1mL / L benzylpyridinium carboxylate, 80mg / L vanillin, 60mg / L polyethylene glycol in the combined brightener, 15g / L potassium sodium tartrate, 2g / L sodium ascorbate, 50mg / L sodium sulfite, 3g / L manganese dichloride in the stabilizer, 0.002mol / L rare earth salt cerium sulfate, 15mg / L tetrahydrothiazolidinethione and 0.15g / L sodium dodecyl sulfate as additives. The water bath temperature is 65°C. After 30 minutes, a bright, smooth and well-bonded high-iron Zn-Fe-P chemical plating layer is obtained on the surface of the 5052 aluminum specimen.
[0046] The results of EDS semi-quantitative analysis showed that the zinc content in the obtained coating was 78.3wt.%, the iron content was 18.3wt.%, the phosphorus content was 1.9wt.%, and the remainder was others.
[0047] The 5052 aluminum test piece covered with a high-iron Zn-Fe-P chemical plating layer was immersed in a low-iron solution for deposition. The composition of the low-iron solution and the subsequent treatment method were the same as those in Example 1.
[0048] It is obvious that those skilled in the art can easily make various modifications to the above embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art to the present invention based on the disclosure of the present invention should be within the protection scope of the present invention.
Claims
1. A Zn-Fe-P chemically plated gradient anti-wear layer, characterized in that: From the surface to the inside, it is divided into a passivation layer, a low-iron Zn-Fe-P chemical plating layer and a high-iron Zn-Fe-P chemical plating layer, forming a gradient plating layer with corrosion potential from low to high; The low-iron Zn-Fe-P chemical plating layer has an iron content of 0.03wt% to 1.0wt%, a thickness of 8μm to 18μm, and a hardness of 120 to 130HV; The high iron Zn-Fe-P chemical plating layer has an iron content of 5wt% to 30wt%, a thickness of 8μm to 18μm, and a hardness of 450 to 550HV.
2. The Zn-Fe-P chemically plated gradient anti-wear layer according to claim 1, characterized in that: The iron content of the low-iron Zn-Fe-P chemical plating layer is 0.1wt% to 1.0wt%, and the iron content of the high-iron Zn-Fe-P chemical plating layer is 7wt% to 20wt%.
3. The Zn-Fe-P chemically plated gradient anti-wear layer according to claim 1 or 2, characterized in that: The high iron Zn-Fe-P chemical plating layer is prepared from the following high iron solution: The high iron solution comprises zinc oxide, sodium hydroxide, ammonium ferrous sulfate hexahydrate, sodium hypophosphite, a multi-component complex system, a combined brightener and a stabilizer; The concentration of zinc oxide is 8-15 g / L; The concentration of the sodium hydroxide is 50-120 g / L; The concentration of the ammonium ferrous sulfate hexahydrate is 18-40 g / L; The concentration of the sodium hypophosphite is 10 to 30 g / L; The multi-component complex system is an alkaline system, which is a mixture of tetraethylenepentamine, triethylenetetramine, ethylenediamine, sodium gluconate and triethanolamine; the concentration of tetraethylenepentamine is 10-30mL / L, the concentration of triethylenetetramine is 0-20mL / L, the concentration of ethylenediamine is 0-20mL / L, the concentration of sodium gluconate is 10-30g / L, and the concentration of triethanolamine is 5-20mL / L.
4. The Zn-Fe-P chemically plated gradient anti-wear layer according to claim 3, characterized in that: In the high iron solution, the concentration of the ammonium ferrous sulfate hexahydrate is 20-30 g / L, the concentration of the sodium hypophosphite is 15-26 g / L, the concentration of tetraethylene pentamine is 15-25 mL / L, the concentration of triethylenetetramine is 0-15 mL / L, the concentration of ethylenediamine is 0-15 mL / L, the concentration of sodium gluconate is 15-20 g / L, and the concentration of triethanolamine is 10-15 mL / L.
5. The Zn-Fe-P chemically plated gradient anti-wear layer according to claim 3, characterized in that: The high iron solution also includes other additives, which are tetrahydrothiazolidine and surfactants; tetrahydrothiazolidine 0-20 mg / L; the surfactant includes one or more of chlorhexidine, OP emulsifier, sodium dodecyl sulfate, and sodium dodecyl sulfonate, with a total concentration of 0.04-0.8 g / L.
6. The Zn-Fe-P chemically plated gradient anti-wear layer according to claim 3, characterized in that: The low-iron Zn-Fe-P chemical plating layer is prepared from the following low-iron solution: The low-iron solution comprises zinc oxide, sodium hydroxide, ammonium ferrous sulfate hexahydrate, sodium hypophosphite, a multi-component complex system, a combined brightener and a stabilizer; The concentration of zinc oxide is 8-15 g / L; The concentration of the sodium hydroxide is 50-120 g / L; The concentration of the ammonium ferrous sulfate hexahydrate is 1.5 to 15 g / L; The concentration of the sodium hypophosphite is 10 to 30 g / L; The multi-component complex system is an alkaline system, which is a mixture of sodium salicylate, sodium citrate or ammonium citrate, pyridine, sodium gluconate and triethanolamine; the concentration of sodium salicylate is 3-18 g / L, the concentration of sodium citrate or ammonium citrate is 10-30 g / L, the concentration of pyridine is 0-18 g / L, the concentration of sodium gluconate is 10-30 g / L, and the concentration of triethanolamine is 10-30 mL / L.
7. The Zn-Fe-P chemically plated gradient anti-wear layer according to claim 6, characterized in that: In the low-iron solution, the concentration of ammonium ferrous sulfate hexahydrate is 2-8 g / L, the concentration of sodium hypophosphite is 15-26 g / L, the concentration of sodium salicylate is 5-12 g / L, the concentration of sodium citrate or ammonium citrate is 12-25 g / L, the concentration of pyridine is 0-12 g / L, the concentration of sodium gluconate is 15-20 g / L, and the concentration of triethanolamine is 15-25 mL / L.
8. The Zn-Fe-P chemically plated gradient anti-wear layer according to claim 6, characterized in that: The low-iron solution also includes a surfactant; the surfactant includes one or more of chlorhexidine, OP emulsifier, sodium dodecyl sulfate, and sodium dodecyl sulfonate, and the total concentration is 0.04-0.8 g / L.
9. The Zn-Fe-P chemically plated gradient anti-wear layer according to claim 1, characterized in that: The passivation layer is prepared from a solution consisting of chromium nitrate nonahydrate, sodium nitrate, sodium oxalate, sodium malonate, maleic anhydride, cobalt nitrate hexahydrate and amino silicon: the concentration of the chromium nitrate nonahydrate is 40-80 g / L; the concentration of the sodium nitrate is 5-20 g / L; the concentration of the sodium oxalate is 10-20 g / L; the concentration of the sodium malonate is 10-20 g / L; the concentration of the maleic anhydride is 1-2 g / L; the concentration of the cobalt nitrate hexahydrate is 5-8 g / L; and the concentration of the amino silicon is 3-5 mL / L.
10. The method for preparing the Zn-Fe-P chemically plated gradient anti-wear layer according to any one of claims 6 to 8, characterized in that: The metal component is first subjected to a pretreatment of degreasing-washing-rust removal-washing-activation, and then immersed in a high-iron solution for deposition after washing to obtain a metal component covered with a high-iron Zn-Fe-P chemical plating layer, and then directly immersed in a low-iron solution for deposition without washing, so that the high-iron Zn-Fe-P chemical plating layer is covered with a low-iron Zn-Fe-P chemical plating layer, and then subjected to light exposure-washing-passivation-washing-sealing-drying after washing, so that the low-iron Zn-Fe-P chemical plating layer is covered with a passivation layer, thereby obtaining a desired Zn-Fe-P chemical plating gradient anti-wear layer on the surface of the metal component; The temperature of deposition in high iron solution is 40-80°C, and the time is 20-40 minutes; the temperature of deposition in low iron solution is 40-80°C, and the time is 30-60 minutes; during passivation treatment, nitric acid or sodium hydroxide is used to adjust the pH value of the solution to 2.0-2.5, the temperature is 20-45°C, and the time is 30-60s.
Citation Information
Patent Citations
Bright corrosion resisting zinc-iron alloy plating process
CN101545125A
Weak acid chloride electroplating solution used for neodymium iron boron electroplating of zinc-iron alloy and preparation method
CN104120466A
Alkaline zinc-iron alloy electroplate liquid, preparation method and electroplating process
CN105442000A
Alkaline graphene zinc-iron alloy electroplating liquid, preparation method and electroplating technology
CN109137016A
Plating solution for electrodepositing bright Zn-Fe alloy with low Fe content from sulfate system
CN1162571C
Cited By
Abrasion-resistant layer and preparation method thereof
CN119753681A